2022
DOI: 10.1590/0102-311xen277321
|View full text |Cite
|
Sign up to set email alerts
|

Association between socioeconomic and nutritional factors and height of Brazilian adolescents: results from the Study of Cardiovascular Risk in Adolescents

Abstract: This study aims to describe the mean height of adolescents from the five regions of Brazil and to evaluate socioeconomic and nutritional factors associated with normal growth. This is a cross-sectional study conducted in the Brazilian urban and rural areas with students aged 12 to 17 years (n = 71,553). Anthropometry, socioeconomic variables, physical activity, and diet were evaluated. Height-for-age z-scores were calculated and multiple linear regression models were used to investigate the association of expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(45 reference statements)
0
0
1
Order By: Relevance
“…While previous studies have primarily focused on body weight, body composition, and related outcomes such as body mass index or fat mass index [10], our study specifically examined linear growth and its association with protein intake. Our findings contradict two earlier cross-sectional studies that reported a positive association between dietary protein intake and linear growth [21,22]. Some prospective studies also reported a positive association between protein intake with height [23][24][25][26].…”
Section: Discussioncontrasting
confidence: 99%
“…While previous studies have primarily focused on body weight, body composition, and related outcomes such as body mass index or fat mass index [10], our study specifically examined linear growth and its association with protein intake. Our findings contradict two earlier cross-sectional studies that reported a positive association between dietary protein intake and linear growth [21,22]. Some prospective studies also reported a positive association between protein intake with height [23][24][25][26].…”
Section: Discussioncontrasting
confidence: 99%